Japan Stock Market Lessons Amid Pandemic and Before - Ihor HURNYAK; Arkadiusz NIEDZWIECKI; Marek PRONIEWSKI (Communications of International Proceedings, 2021)
The new conditions in which the economy has been affected by the pandemic restrictions require a new look at traditional time-tested instruments such as a stock market. The Japanese stock market is a great example of overcoming problems and confident self-swimming. Its work can be analyzed on the basis of modern tools. Using a Fama – French method a chosen portfolio of shares was tested and a range of methods has been used to predict the shares prices. A wide list of Python language packages was applied, which allowed the use of significant statistical data on the base of well-known tickers of companies. Parallel processes in the Japanese and American markets, and excessive fluctuations in the price and return of Japanese shares in European markets were revealed. The Japanese experience clearly indicates the need to develop own stock market, avoiding imposed by the negative experience or external beliefs in the hopelessness of forming it by even negative circumstances. As a result Japanese business in its own market is more predictable in terms of price than the issuance of its shares abroad. For comparison has been revealed the fact that the Chinese market is less suitable for analysis based on traditional optimization methods. We did not find in this case a significant impact of the pandemic on price dynamics. This impact was short-term without serious consequences.
Keywords: Japan economy; Fama – French; stock market; portfolio optimization